Bruton’s Tyrosine Kinase Inhibitors Impair FcγRIIA-Driven Platelet Responses to Bacteria in Chronic Lymphocytic Leukemia - Naylor-Adamson, Leigh; Chacko, Anisha R.; Booth, Zoe; Caserta, Stefano; Jarvis, Jenna; Khan, Sujoy; Hart, Simon P.; Rivero, Francisco; Allsup, David J.; Arman, Mònica (Frontiers in Immunology, 2021)
Bacterial infections are a major cause of morbidity and mortality in chronic lymphocytic leukemia (CLL), and infection risk increases in patients treated with the Bruton's tyrosine kinase inhibitor, ibrutinib. Btk and related kinases like Tec are expressed in non-leukemic hematopoietic cells and can be targeted by ibrutinib. In platelets, ibrutinib therapy is associated with bleeding complications mostly due to off-target effects. But the ability of platelets to respond to bacteria in CLL, and the potential impact of ibrutinib on platelet innate immune functions remain unknown. FcγRIIA is a tyrosine kinase-dependent receptor critical for platelet activation in response to IgG-coated pathogens. Crosslinking of this receptor with monoclonal antibodies causes downstream activation of Btk and Tec in platelets, however, this has not been investigated in response to bacteria. We asked whether ibrutinib impacts on FcγRIIA-mediated activation of platelets derived from CLL patients and healthy donors after exposure to Staphylococcus aureus Newman and Escherichia coli RS218. Platelet aggregation, α-granule secretion and integrin αIIbβ3-dependent scavenging of bacteria were detected in CLL platelets but impaired in platelets from ibrutinib-treated patients and in healthy donor-derived platelets exposed to ibrutinib in vitro. While levels of surface FcγRIIA remained unaffected, CLL platelets had reduced expression of integrin αIIbβ3 and GPVI compared to controls regardless of therapy. In respect of intracellular signaling, bacteria induced Btk and Tec phosphorylation in both CLL and control platelets that was inhibited by ibrutinib. To address if Btk is essential for platelet activation in response to bacteria, platelets derived from X-linked agammaglobulinemia patients (lacking functional Btk) were exposed to S. aureus Newman and E. coli RS218, and FcγRIIA-dependent aggregation was observed. Our data suggest that ibrutinib’s impairment of FcγRIIA-mediated platelet activation by bacteria results from a combination of Btk and Tec inhibition, although off-target effects on additional kinases cannot be discarded. This is potentially relevant to control infection-risk in CLL patients and, thus, future studies should carefully evaluate the effects of CLL therapies, including Btk inhibitors with higher specificity for Btk, on platelet-mediated immune functions.